2014
DOI: 10.1186/2196-4351-2-2
|View full text |Cite
|
Sign up to set email alerts
|

Interface evaluation of experimental dental adhesives with nanostructured hydroxyapatite incorporation

Abstract: The aim of this study was to evaluate the adhesive interface with dentin of an experimental adhesive resin with nanostructured hydroxyapatite addition. The organic phase of the adhesive resin was produced by mixing 50 wt.% Bis-GMA, 25 wt.% TEGDMA and 25 wt.% HEMA. CQ and EDAB were added at 1 mol% to all groups, according to the monomer moles. HA nano was added at the following two concentrations: 0 and 2 wt%. One commercial adhesive system was used as control. Nine lower incisor bovine teeth were used to produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…11,12 Although some researchers have reported the possible use of nanofillers in dental adhesives, their use remains a challenge due to the still limited number of fillers used for this purpose. 6 Therefore, the aim of this study was to investigate the effect of the concentration and type of organomodified montmorillonite clays in the adhesion layer on the mechanical properties of dental adhesives.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 Although some researchers have reported the possible use of nanofillers in dental adhesives, their use remains a challenge due to the still limited number of fillers used for this purpose. 6 Therefore, the aim of this study was to investigate the effect of the concentration and type of organomodified montmorillonite clays in the adhesion layer on the mechanical properties of dental adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Besides this, because of their small sizes, nanoparticles are able to penetrate into the tooth micropores, providing a bond layer with improved properties. 6,10 Clay-polymer systems can show improvement of many properties of polymeric matrixes, such as elastic modulus, flexural and tensile properties and heat resistance. Clay systems have many possible morphologies, which include: (1) agglomerated particles, where the layers remain joined and polymer chains only interact with their surface; (2) intercalated, when the polymer chains are between the clay platelets; and (3) exfoliated, when the silicate platelets are isotropically dispersed in the polymeric matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These main class polymers comprise bioresorbable compounds known as alpha-polyesters or poly(alpha-hydroxy) acids [85], and poly (acrylonitrile-co-butadiene-co-styrene) (ABS) [86]. Many studies reported that polymers modified with HA filler improve the mechanical properties, such as tensile strength, flexural strength, impact energy and hardness, as well as biocompatibility of composites [23,27,[87][88][89][90]. This finding can be ascribed to the excellent biocompatibility of HA [91].…”
Section: Biomedical Applications Of Polymer/ha Compositesmentioning
confidence: 99%
“…Niobium pentoxide (Nb 2 O 5 , Companhia Brasileira de Metalurgia e Mineração, Araxá, MG, Brazil) was added at 2.5 and 5 wt%, in relation to the mass of the experimental adhesives, and one adhesive without Nb 2 O 5 was used as a control. Nb 2 O 5 was previously silanized using γ-methacryloxypropyltrimethoxysilane (γ-MPTS, Aldrich Chemical Co., Milwaukee, WI, USA) [17]. Reagents were hand mixed and sonicated for 180 s.…”
Section: Formulation Of Experimental Adhesivesmentioning
confidence: 99%